2019
DOI: 10.1177/1076029619850897
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of US Hospitalized Medically Ill Patients Who May Qualify for Extended Thromboprophylaxis

Abstract: Extended thromboprophylaxis with oral anticoagulation can reduce the risk of symptomatic venous thromboembolism (VTE) in high-risk patients. We sought to estimate the proportion of medically ill patients in the United States who might qualify for extended thromboprophylaxis according to the criteria used in the Medically-Ill Patient Assessment of Rivaroxaban versus Placebo in Reducing Post-Discharge Venous ThromboEmbolism Risk (MARINER) trial. We analyzed 2014 National Inpatient Sample (NIS) data that provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…Thus, our results would further define $60% of an at-VTE risk population of medically ill patents that would benefit from both in-hospital and ET, or $25 to 30% of the total population of medically ill patients. 1,2 The modified IMPROVE VTE risk score plus elevated D-dimer used in our study has the potential to be incorporated as a clinical decision support tool within a health system's electronic health records both at admission and at discharge, where previous efforts in hospitalized medical patients have shown an increase in uptake of appropriate thromboprophylaxis as well as a decrease in VTE using electronic or physician alerts at admission and discharge. 21,22 Limitations of the present analysis include its retrospective design in a subpopulation of the original MAGELLAN study population, which can introduce recall bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our results would further define $60% of an at-VTE risk population of medically ill patents that would benefit from both in-hospital and ET, or $25 to 30% of the total population of medically ill patients. 1,2 The modified IMPROVE VTE risk score plus elevated D-dimer used in our study has the potential to be incorporated as a clinical decision support tool within a health system's electronic health records both at admission and at discharge, where previous efforts in hospitalized medical patients have shown an increase in uptake of appropriate thromboprophylaxis as well as a decrease in VTE using electronic or physician alerts at admission and discharge. 21,22 Limitations of the present analysis include its retrospective design in a subpopulation of the original MAGELLAN study population, which can introduce recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is estimated that approximately one-quarter of hospitalized medically ill patients are at high VTE risk. 1,2 Data from randomized controlled trials of ET with the direct oral anticoagulants (DOACs) betrixaban and rivaroxaban reveal net clinical benefit of such a strategy in key patient groups or subgroups, and these agents have gained regulatory approval in the US. 3,4 However, identification of such patients using a standardized approach remains difficult.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous clinical trials have assessed the validity of prolonging VTE prophylaxis posthospital discharge and compared current available therapeutic agents for efficacy. [4][5][6][7] As hospitalization is the highest ranked risk factor for the development of VTE, use of VTE prophylaxis for acutely ill medical patients has become a standard of care. 8 Standard prophylaxis is given during hospitalization based on certain risk characteristics, such as a current diagnosis of pneumonia, acute respiratory failure, heart failure, or history of stroke among other criteria associated with increased VTE risk in the acute medically ill population.…”
Section: Introductionmentioning
confidence: 99%
“…Current data show both apixaban and rivaroxaban are noninferior to traditional enoxaparin for short durations (10-14 days) postdischarge but notably showed no benefit for a prolonged duration (30-35 days) and increased the incidence of bleeding. [4][5][6][7] An additional clinical trial looked at the efficacy of a new comer, betrixaban, for reducing the risk of VTE postdischarge in a subset of patients considered to be at high risk for VTE prophylaxis. 15 Investigators found benefit in patients with elevated D-dimer or aged over 75 years and in the younger patients with specific risk factors such as a history of VTE or a history of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation